Structural evaluation and animal implantation of porous eggshell wastederived hydroxyapatite graft as bone substitution - Rahadyan Magetsari, Yudha Mathan Sakti (Universitas Gadjah Mada, 2013)
The development of hydroxyapatite graft with high economically value is needed for orthopedic practice in developing countries. Eggsell waste is well known as natural substance for calcium resource. It has been used as raw material in producing hydroxyapatite. This study was conducted to synthesize porous hydroxyapatite from eggshell waste and evaluate its activity as bone substitution. The porous hydroxyapatite graft was manufactured from eggshell and sugar as a raw material using hydrothermal process. The porous eggshell waste-derived hydroxyapatite (EW-HAP) graft was characterized using X ray difractometer (XRD) and analytical scanning electron microscope (SEM) and compared with commercial hydroxyapatite (HAP) JCPDS 09-432 graft (Bangros®) as standard. The porous EW-HAP graft obtained was then implanted on critically sized femoral defects surgically created in the right thigh of male Wistar rats (Rattus norvegicus) with Bangros® as control. Radiological examination using XRD and histological examination using hematoxyline-and-eosin staining of the bone femour were performed at 28 days after implantation. The results showed that the XRD pattern for EW-HAP was likely similar with the HAP standard. However, the SEM examination showed that the pasticle size of EW-HAP graft (2.5-3 μm) was higher than those HAP standard graft (1.5-2 μm). Radiographs according to the International of Limb Salvage (ISOLS) radiological evaluation system between EW-HAP graft (6.1 ± 1.45) and HAP control graft (6.9 ± 2.10) was not significantly different (p>0.05). Moreover, histological examination according to Lane and Shandu scoring system between the both graft (4.0 ± 0.94 versus 4.4 ± 0.92) was also not significantly different (p>0.05). It can be concluded that the structure EW-HAP graft is similar with HAP graft standard. The both grafts have also equal outcome as bone substitution.